2015
DOI: 10.1371/journal.pone.0139133
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 60 in Eggs Specifically Induces Tregs and Reduces Liver Immunopathology in Mice with Schistosomiasis Japonica

Abstract: BackgroundParasitic helminths need to suppress the host immune system to establish chronic infections. Paradoxically, immunosuppression induced by the worm also benefits the host by limiting excessive inflammation and tissue damage, which remains the major cause leading to serious morbidity and mortality. Regulatory T cells (Tregs) are key immune regulators of this mutualism. The successive rise in Tregs during schistosome infection plays a critical role in immunoregulation. We and others previously showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
2
22
2
Order By: Relevance
“…Similarly, our previous study demonstrated that APCs, for example, Mφ or DC, are necessary in SjHSP60, a major S. japonicum egg antigen, mediated conversion of CD4 + CD25 À T cells into Tregs. 30 Here, our result further showed that in contrast to lipopolysaccharide-stimulated Mφ (LPS-Mφ), SjHSP60-treated Mφ (SjHSP60-Mφ) retained an immature morphology with a more rounded shape (Supplementary figure 1c). FCM (flow cytometry) analysis revealed that less profoundly increased expression of MHC class II and co-stimulatory molecules (CD40, CD80 and CD86), but more significant upregulation of co-inhibitory molecule (programmed death ligand 1, PD-1/B7-H1) on SjHSP60-Mφ (Supplementary figure 1d).…”
Section: Sjhsp60-treated Mφ Display a Tolerogenic Phenotype Charactersupporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, our previous study demonstrated that APCs, for example, Mφ or DC, are necessary in SjHSP60, a major S. japonicum egg antigen, mediated conversion of CD4 + CD25 À T cells into Tregs. 30 Here, our result further showed that in contrast to lipopolysaccharide-stimulated Mφ (LPS-Mφ), SjHSP60-treated Mφ (SjHSP60-Mφ) retained an immature morphology with a more rounded shape (Supplementary figure 1c). FCM (flow cytometry) analysis revealed that less profoundly increased expression of MHC class II and co-stimulatory molecules (CD40, CD80 and CD86), but more significant upregulation of co-inhibitory molecule (programmed death ligand 1, PD-1/B7-H1) on SjHSP60-Mφ (Supplementary figure 1d).…”
Section: Sjhsp60-treated Mφ Display a Tolerogenic Phenotype Charactersupporting
confidence: 68%
“…[25][26][27][28] Our previous studies also have shown that the S. japonicum stress protein HSP60 (heat shock protein 60, SjHSP60) and a SjHSP60derived peptide SJMHE1 significantly induce immunosuppressive Tregs both in vitro and in vivo through TLR on APCs (Mφ or dendritic cells, DCs) by inducing higher levels of TGF-b. 29,30 However, whether and how schistosome antigens manipulate TLR signaling to promote TGF-b production in APCs and thereby induce Tregs remains to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that regulatory T cells play an important repressor role in the down‐regulation of pathological immune responses at this stage. Previous studies have shown that regulatory T cells and their functional factor IL‐10 could prevent the response of Th1, Th2 and Th17 . Hence, the schistosome‐induced hepatic pathology is regulated by multiple cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that regulatory T cells and their functional factor IL-10 could prevent the response of Th1, Th2 and Th17. 18,19 Hence, the schistosome-induced hepatic pathology is regulated by multiple cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…The IP of MIC3 from ESAs was performed as described previously with some modification59. For a single IP, 20 μl mouse monoclonal antibody to T. gondii MIC3 (anti-MIC3 mAb, GeneTex) was incubated with 200 μl protein G-agarose suspension (Sigma-Aldrich, St. Louis, MO, USA) at 4 °C for 3 h. Next, anti-MIC3 mAb conjugated to the protein G-agarose suspension was collected by centrifugation, mixed with ESAs (200 μg) and incubated with mixing at 4 °C for 3 h. Finally, the protein G-agarose was removed by centrifugation.…”
Section: Methodsmentioning
confidence: 99%